2007
DOI: 10.1196/annals.1423.010
|View full text |Cite
|
Sign up to set email alerts
|

X Monosomy in Female Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a systemic autoimmune disease, predominantly occurring in women of childbearing age. SLE, like several other autoimmune diseases, is characterized by a striking female predominance and, although sex hormone influences have been suggested as an explanation for this phenomenon, definitive data are still unavailable. Our group recently reported an increased X monosomy in lymphocytes of women, affected with primary biliary cirrhosis (PBC), systemic sclerosis (SSc), and autoimm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 17 publications
0
34
1
Order By: Relevance
“…Nevertheless, it is possible that this is not true for any AID as we failed to confirm the finding in women suffering for SLE [43,44]. In one of this AID, PBC, we have also demonstrated that X chromosome is preferentially lost, thus ruling out the possibility that a specific haplotype on X chromosome could trigger AID in a predisposed subject.…”
Section: Chromosome and Aid: When The Number Is The Problemcontrasting
confidence: 73%
See 1 more Smart Citation
“…Nevertheless, it is possible that this is not true for any AID as we failed to confirm the finding in women suffering for SLE [43,44]. In one of this AID, PBC, we have also demonstrated that X chromosome is preferentially lost, thus ruling out the possibility that a specific haplotype on X chromosome could trigger AID in a predisposed subject.…”
Section: Chromosome and Aid: When The Number Is The Problemcontrasting
confidence: 73%
“…In one of this AID, PBC, we have also demonstrated that X chromosome is preferentially lost, thus ruling out the possibility that a specific haplotype on X chromosome could trigger AID in a predisposed subject. At this point, we still need to determine the parental origin of the remaining chromosome mainly because the disease is characterized by a relatively old mean age at diagnosis with consequent difficulty in obtaining DNA from parents [43]. We believe that the progressively acquired haploinsufficiency for genes on X chromosome in immune-related cells is a mechanism for immunosenescence, the state of altered immune function of the elderly known to concur to the increased susceptibility to infection, cancer, and the onset of AID [33,45].…”
Section: Chromosome and Aid: When The Number Is The Problemmentioning
confidence: 99%
“…It is also notable that increased X monosomy rates have been found more frequently in peripheral T and B lymphocytes than in other blood cell populations without evidence of microchimerism that would explain the existence of the monosomic cells [100e105]. However, these findings could not be duplicated in a study of female patients with SLE, in which the authors proposed that the methylation pattern rather than the monosomy of the X chromosome, along with other hypotheses, might have a more preponderant role in female biased autoimmunity, but this needs further research [104]. Invernizzi et al offers an explanation of how X monosomy might be associated with autoimmunity by hypothesizing that X chromosome monosomy may cause a haploinsufficiency in X-linked genes that escape X chromosome inactivation and, as a consequence, autoreactive T cells are not exposed to self-antigens encoded by one of the two X chromosomes.…”
Section: Multiple Sclerosismentioning
confidence: 91%
“…Our group has mostly focused on the latter, identifying peculiar patterns of X chromosome loss in peripheral cells of individuals affected by several autoimmune diseases [11e13], including autoimmune thyroiditis (AIT). Nonetheless, some other conditions, such as systemic lupus erythematosus (SLE) did not display haploinsufficiency at increased rates compared to the general population [14] but, on the contrary, an increased dose of X chromosomes [15].…”
Section: Introductionmentioning
confidence: 98%